On the Welfare Effects of Monetary Policy When Households Try to Keep Up with the Rest of the World - Christian Pierdzioch; Serkan Yener (Kiel Institute for World Economics (IfW), 2004)
We develop a dynamic general equilibrium two-economy model in order to analyze the welfare effects of monetary policy in open economies. The model features two distortions: one distortion due to monopolistic competition, and one distortion due to a consumption externality. This consumption externality arises because households' preferences feature a ?keeping up with the rest of the world? effect. This effect implies that households' utility depends upon the level of their consumption relative to the average consumption in the world. We show that, depending on the relative magnitude of the monopolistic distortion and the consumption externality, an expansive monetary policy can result in an increase or a decrease of households' welfare.
Keywords: F41; F42; 330; Monetary policy; Consumption externality; Welfare effects; Geldpolitik; Konsuminterdependenz; Wohlfahrtseffekt; Neue Makroökonomik offener Volkswirtschaften; Zwei-Länder-Modell; Dynamisches Gleichgewicht; Theorie